Development of simultaneous localization and mapping with collision avoidance for unmanned aerial vehicle application - Khoo, Hung Siang, 1996-, author; Istas Fahrurrazi Nusyirwan, supervisor; Fakulti Kejuruteraan. Sekolah Kejuruteraan Mekanikal (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2019